Geschichte der venezianischen Malerei, Band 3 Von Giorgione zum frühen Tizian - Brucher, Günter (2013)
Giorgione remains the central figure in the scientific discussion dealing with Venetian painting of the age, and accordingly the amount of literature on him is exuberant. The state of scientific discussion which harks back well into the 19th century, proves to be very heterogeneous, a selection of statements proves to be inapt as to serve as a basis for a further critical discussion. The outcome of all this is a general dissent, caused by the poor state of sources and the comparatively small number of secured works. In consequence, we are confronted with a constant struggle of attributions, increasing and decreasing in number, and a host of dates, often contradictory.